Making sense of Turkey's cautious reaction to power shifts in Tunisia: Turkey adjusts its foreign policy in Europe's southern neighbourhood - Nebahat Tanrıverdi Yaşar; Hürcan Aslı Aksoy (Stiftung Wissenschaft und Politik (SWP), 2021)
Ankara adopted notably toned-down language towards Tunisian President Kaïs Saïed's power grab and avoided calling it a coup, although it considers the course of events as a potential threat that could endanger its policies towards North Africa. In fact, Turkey revised its approach to Tunisia after secular parties became more prominent in Tunisian politics following the 2014 elections. This policy adjustment consists of developing a balanced network of relations by reaching out to secular parties on the one hand, but retaining close ties with the Islamist Ennahda party on the other hand. To this end, Ankara is giving weight to defence diplomacy and soft power. This tactful approach is in line with Turkey's efforts to strengthen its geostrategic and geo-economic ties with the Maghreb countries and overlaps with ongoing normalisation efforts between Ankara and Arab capitals. But this approach is limited to a pragmatic policy adjustment. Germany and other European states should see this as an opportunity to encourage regional de-escalation and contribute to a constructive regional dialogue.
Keywords: 320